2010
DOI: 10.4049/jimmunol.0903831
|View full text |Cite
|
Sign up to set email alerts
|

CXC Chemokine Ligand (CXCL) 9 and CXCL10 Are Antagonistic Costimulation Molecules during the Priming of Alloreactive T Cell Effectors

Abstract: Donor Ag-reactive CD4 and CD8 T cell production of IFN-γ is a principal effector mechanism promoting tissue injury during allograft rejection. The CXCR3-binding chemokines CXCL9 and CXCL10 recruit donor-reactive T cells to the allograft, but their role during the priming of donor-reactive T cells to effector function is unknown. Using a murine model of MHC-mismatched cardiac transplantation, we investigated the influence of CXCL9 and CXCL10 during donor-reactive T cell priming. In allograft recipient spleens, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 56 publications
2
61
1
Order By: Relevance
“…In addition to the role of CXCL9/ CXCL10 in the recruitment of T cells to the allograft, Rosenblum et al (2010) recently showed that these chemokines regulate donor-specific CD8 þ T-cell priming. As such, in a murine model of cardiac transplantation using KO mice for either the CXCL9 or CXCL10 gene, CXCL9 promoted, whereas CXCL10 inhibited the differentiation of IFN-g-producing donor-specific CD8 þ T cells.…”
Section: Chemokinesmentioning
confidence: 99%
“…In addition to the role of CXCL9/ CXCL10 in the recruitment of T cells to the allograft, Rosenblum et al (2010) recently showed that these chemokines regulate donor-specific CD8 þ T-cell priming. As such, in a murine model of cardiac transplantation using KO mice for either the CXCL9 or CXCL10 gene, CXCL9 promoted, whereas CXCL10 inhibited the differentiation of IFN-g-producing donor-specific CD8 þ T cells.…”
Section: Chemokinesmentioning
confidence: 99%
“…Chemokine (C-X-C motif) ligand 10 (CXCL10) as a major chemokine, as well as the absence of acid-leucine-arginine peptide chemokine, detected in an allograft and isograft model, was found to accelerate acute allograft rejection after organ transplantation (9-11); this occurred via binding to the G-protein-coupled receptor CXCL receptor 3 (CXCR3), which was expressed in multiple cells such as primed effector T cells producing interferon (IFN)-γ and Tm cells (11,12). CXCL10 has been demonstrated to have an important role in the generation of T lymphocyte effector functions in infection and first transplants (13); however, few, if any, experimental and clinical studies on the role of CXCL10 in accelerated rejection mediated by Tm cells are available.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the expression pattern of these chemokines in tissues during inflammation is different (36)(37)(38). Recent studies in a murine cardiac allograft model demonstrated antagonistic effects of Mig and IP-10 on the costimulation of alloreactive IFN-gproducing CD8 T cells (39), and we recently observed differential effects of these two chemokines on the activation of tumorspecific T cells as well (A. Gorbachev, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 95%